The Effect of Judo on the Self-Confidence of Athletes with Disabilities: A Perspective from Self-Efficacy Theory - Tony Ricardo Mantolas; Mochamad Ridwan; Taufiq Hidayat (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2025)
Low self-confidence remains a major challenge in the development of athletes with disabilities, particularly in the context of competitive sports. Low self-confidence can hinder motivation, reduce performance, and increase the risk of social isolation. While sports are believed to improve psychological aspects, there have been few studies that specifically evaluate the impact of martial arts such as judo on the self-confidence of athletes with disabilities. This study aims to examine the influence of participation in judo on the self-confidence of athletes with disabilities, particularly those who are visually impaired, based on the theory of self-efficacy. The study employs a pre-experimental one-group pretest-posttest design, involving 11 national judo team athletes as subjects. Data were collected through a self-efficacy questionnaire covering four dimensions: mastery experience, vicarious experience, verbal persuasion, and physiological-emotional conditions. The results showed an average decrease in scores from 60.18 to 58.73; however, the increase in maximum scores and response variability post-intervention indicated complex individual dynamics. These findings indicate that judo has potential as a tool for psychological strengthening, but requires a more personalized training approach and integrated psychological support. This study suggests the need for further research using stronger experimental methods and a broader population to gain a more comprehensive understanding.